Conceiving resilience: Lexical shifts and proximal meanings in the human-centered natural and built environment literature from 1990 to 2018. (February 2020) - Wang, Yan; Hulse, David; Von Meding, Jason; Brown, Madeline; Dedenbach, Laura
Abstract: The complex dynamics of the human-centered natural and built environment (HNBE) have been characterized by emerging and diverging conceptions of resilience (e.g., climate resilience, disaster resilience, social-ecological resilience). Each resilience modifier has produced rich bodies of literature, drawing on distinctive meanings of the term "resilience." As resilience modifiers have continued to multiply and evolve over the past three decades, the relationships among them have become less clear. This impedes effective management of resilience in a more integrated HNBE. To improve understanding of the evolution and commonalities of resilience modifiers, we surveyed 3, 181 articles concerning seven resilience modifiers published from 1990 to 2018. Using bibliometric analysis tools, we clarify lexical meanings of these resilience concepts and find a convergence among them based on their shared concerns and intellectual genealogy. This converging conception of resilience may motivate and catalyze more integrated knowledge, methods, and expertise in understanding and managing resilience across disciplines. Highlights: Conducted an overview of conceptions of resilience in 3000 articles across disciplines using bibliometric analysis and visualization. Reviewed literature across seven resilience modifiers over 29 years that focused on human-centered natural and built environment. Found similar word usages and proximal meanings by examining author-defined keywords across categories. Identified a shared intellectual genealogy of bibliographic sources.